Construction and Validation of a Ferroptosis-Related Prognostic Model for Endometrial Cancer - Wang, Hao; Wu, Yingchen; Chen, Shengfu; Hou, Minzhi; Yang, Yanning; Xie, Meiqing (Frontiers in Genetics, 2021)
Endometrial cancer (EC) is one of the most common female reproductive system tumors, with close to 200,000 new cases each year. It accounts for about 7% of the total number of female cancers, but until now, the cause of endometrial cancer is still unclear. Ferroptosis is a kind of regulated cell death that distinguish with apoptosis and oxidative damage. The process has unique biological effects on metabolism and redox biology. In this study, we analyze the relation between endometrial cancer and ferroptosis. According to the different expression levels of related genes, we first divide 544 cases of endometrial cancer samples into 4 clusters, and find that most of the immune infiltrating cells had significant differences in the four groups. The gene expression difference analysis between Fe.cluster groups was performed, and the samples were again divided into three Fe.Gene.cluster. The molecular characteristics and clinical characteristics of the groups are significantly different. Finally, 13 characteristic genes were selected as Ferroptosis gene signatures and get Fe.score by calculation. Fe.score is closely related to the clinical and molecular characteristics of EC, and low Fe.score has a significant survival advantage; GDSC predicts that the IC50 of multiple chemotherapeutic drugs is also significantly different between the two groups. Overall, our research has explored the relationship between endometrial cancer and ferroptosis in detail, and establish a novel EC prognosis model, which can improve the prognosis and clinical management of EC patients.